Biology of the crab Leurocyclus tuberculosus (H. Milne Edwards & Lucas, 1843) bycatch from pink shrimp trawl fishery in the coast of Rio de Janeiro, Brazil - Stauffer,Tainá (2011)
Trawling is known as one of less selective fishing gears and presents high index of accidental captures. The objective of this paper is to characterize the population structure, fecundity and relative growth of Leurocyclus tuberculosus often caught as bycatch in pink shrimp trawl. Sampling occurred between October 2008 and September 2009 in the coast of Rio de Janeiro State, using commercial shrimp trawl. The sample totalized 269 crabs, 168 males and 101 females (42 ovigerous). The sex ratio was 1:1.66 (M:F) and differed statistically from the expected (X²=16.68; p > 0.05). The carapace width (CW) ranged from 12.81 to 71.67 mm (mean ± SD: 48.77 ± 13.75 mm) and from 15.33 to 55.44 mm (36.19 ± 8.66 mm) in males and females, respectively. The size at onset of sexual maturity was estimated at 30 mm (females) and 55 mm (males). The individual fecundity ranged from 3,450 to 23,680 eggs/brood (10,327.3 ± 4,827.7). The analysis of relative growth did not differ from the Brachyura predictions. The histogram analysis showed that shrimp trawl affects the L. tuberculosus population equally, capturing from very young individuals to adults.